2019
DOI: 10.1371/journal.pone.0210338
|View full text |Cite
|
Sign up to set email alerts
|

Pulp response of rats submitted to bleaching and the use of different anti-inflammatory drugs

Abstract: This study aimed to evaluate neuropeptide expression after bleaching treatment using histopathological and immunohistochemical analyses and the effects of hydrocortisone and acetaminophen on pulp inflammation, sine dental bleaching and inflammation first occur, and only then, the treatmentt. Sixty-three rats were divided into three groups (n = 21) according to the pain-relieving therapy used: I-control; II-topical application of Otosporin for 10 min after the bleaching treatment; III-oral administration of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…Carbamide peroxide was introduced as an alternative to the traditional hydrogen peroxide, and its use has become widespread [7]. Carbamide peroxide is unstable and breaks down immediately upon contact with tissue and saliva, first dissociating into hydrogen peroxide and urea and subsequently into oxygen, water, and carbon dioxide [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Carbamide peroxide was introduced as an alternative to the traditional hydrogen peroxide, and its use has become widespread [7]. Carbamide peroxide is unstable and breaks down immediately upon contact with tissue and saliva, first dissociating into hydrogen peroxide and urea and subsequently into oxygen, water, and carbon dioxide [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…These types of anti‐inflammatory drugs exert their pharmacological effect at the genomic level, either through binding to glucocorticoid recognition elements (GRE) in DNA, inducing the transcription and translation of anti‐inflammatory proteins (Charmandari, 2012) or by suppressing the expression of pro‐inflammatory genes, by inhibiting transcription factors, such as NF‐κB (Biddie et al, 2012), thus avoiding the synthesis of pro‐inflammatory mediators, such as TNF‐α, as well as the expression of COX‐2, with the subsequent inhibition of the synthesis of PGE 2 (Muñoz‐Carrillo et al, 2017a). Various studies have shown that glucocorticoids are effective for the treatment of pulp inflammation (Gallinari et al, 2019), as well as for the reduction of the periapical inflammatory response after endodontic treatment (Holland, 1996; Marshall, 2002). The results agree with that reported in the literature since, in the present study, treatment with dexamethasone significantly decreased (* p < .05) the levels of PGE 2 and TNF‐α at the systemic level, both at 14 and 18 hours, after pulp damage.…”
Section: Discussionmentioning
confidence: 99%
“…The pulp necrosis caused in this way is the state of dying cell elements of the pulp due to the ichemy, and should be differentiatd from the pup gangrene which is dominantely accompanied by the direct toxic and necrotic effect of the microorganism. It follows from this that anti-inflammatory therapy is completely sufficient and even causal in this case.That is, by stopping the inflammation, the whole cascade of unwanted events which can potentially be caused by the teeth bleaching (20)(21).…”
Section: The Teeth Bleaching Effects and The Biological Response Of T...mentioning
confidence: 99%
“…Scientists have come up with the solution of this problem by measuring and following the level of specific protein molecules which are released during the inflammatory process and are in the direct connection with the promotion of the pain sensation. These are the substance P and the calcitonin related peptide (CGRP -calcitonin gene-related peptide) (20)(21).…”
Section: Introductionmentioning
confidence: 99%